An accurate ab initio electronic structure calculation for interstellar argonium. (September 2019) - Terashkevich, V.A.; Pazyuk, E.A.; Stolyarov, A.V.; Wiebe, D.S.
Highlights: The work provides an ab initio adiabatic potential, permanent dipole moment and static dipole polarizability for the ground state of argonium (ArH + ) over a wide range of interatomic distances. The present results could be useful to estimate the downward cascade radiative transitions as well as the radiative association and dissociative recombination rates for the astronomically important ArH + isotopologues. Graphical abstract: Abstract: A high level electronic structure calculation of the Born–Oppenheimer (BO) potential, scalar-relativistic effect and adiabatic correction is performed for the X 1 Σ + ground state of astronomically important isotopologues of the ArH + cation. Particular attention is paid to both short and long distances, where experimental spectroscopic data is not yet available. The BO energy is obtained over a wide range of interatomic distances ( R ∈ [0.5, 20] Å) in the framework of multi-reference coupled pair functional (MR-ACPF) and single-reference coupled-cluster (CCSD(T)) methods. The all-electrons basis sets of the def2- n ZVPP ( n = 3, 4 ) and n ZaPa-NR, aug-cc-pCV n Z ( n = 3 − 6 ) quality are used to monitor energy convergence. The BO energies are corrected for the basis set superposition error (BSSE) via the counterpoise method and are reduced to the complete basis set (CBS) limit using alternative extrapolating schemes. The permanent dipole moment d ( R ) and static dipole polarizability α ( R ) are calculated using a finite-field method. The molecular structure parameters coincide with their empirical counterparts for low vibrational levels to within 0.1%. Implementation of the ab initio results to circumscribe our understanding of the chemical networks in interstellar space is discussed.